Employment integration experiences of Syrian refugee women arriving through Canada's varied refugee protection programmes. Issue 3 (17th February 2021) - Senthanar, Sonja; MacEachen, Ellen; Premji, Stephanie; Bigelow, Philip
ABSTRACT: This article examines the employment integration experiences of Syrian refugee women arriving to Canada through four common refugee streams: government-assisted, private sponsorship, Blended Visa office referral, and as refugee claimants. Drawing on in-depth, semi-structured interviews with Syrian refugee women and key informants, we show how differences between streams – eligibility requirements, supports provided, services rendered – facilitate or act as barriers to seeking out and securing employment. The finding suggests that government-assisted refugee women struggled the most when compared with the other refugee women. Particularly, GAR women arrived with part of their families and minimal supports, affecting their mental well-being and job search. Meanwhile, the other refugee women typically arrived with the qualities (language, work experience) needed to integrate and so, were able to choose when, how, and the type of work they secured. Through this study, we propose policy recommendations that should be incorporated within the Canadian refugee system to mediate challenges and promote a positive resettlement experience for all refugees.